Desempenho de bezerros mestiços recebendo soro de queijo em pó associado ao leite em pó na fase de aleitamento - Moura, Andrezza Kyarelle Bezerra de (2013)
The present workaimed at evaluatingthe performance and yieldofcarcasscomponentsand no carcasscrossbred calvesreceivingcheese wheypowderassociated withpowdered milkduring sucklinguntil 60and 150 days, besides the realizationof economic analysisof substitution.A total of 40male calves, Holstein xwithoutdefined breed, distributed ina completely randomized designwith fourtreatments and tenreplications: whole milk(control), milk powder,milk powder80% +20% cheese wheypowder;60%milk powder+ 40%cheese wheypowder.After 60 days(suckling), 40test animalswere kept16animalsdivided into twotreatments with eight replicates: confinementandpasturewill, to evaluate the performancephaseofweaning.The developmentof the calveswas evaluated throughweeklyweighingandbodymeasurementsofwithers height, rump height, heart girthandbody length. Afterweaningweighingswere carried out fortnightlyup to 150days.To estimateconsumptionmeasurements were madedailyconsumption ofhay andconcentratedby the methodsupply /spare.The animals wereslaughteredat 60 days, where they weretakenmeasurespHand temperatureof thehot carcass, after 24 hoursofcoldcarcasses. Were also evaluatedparameters forcarcassandno carcass components.Theeconomic performance assessmentconsistedof the calculationof indicatorsof costs and revenues, andmeasuresofeconomic outcomes. All variablesweretested withTukeymean comparison, 5% probability.Theweekly consumption oftotal dry matteringestedweight gainandbody measurementsevaluatedshowed nodifferencesbetween treatments(P>.05). Therewereno significant differences (P>0.05) between treatmentsfor the variablesfor carcass traitsandnon-carcass components. The treatment containing20%cheese wheypowder+80% milk powder and40% cheese wheypowder+60% milk powder hadadditional profitof R$ 116.86and114.24respectively, principallyattributed to thefactthatspending onliquid diet. The results showthat the substitution ofwhole milkcheese wheypowder andits association withmilk powder, shownas avery feasible alternativeand not causing anany influenceon the parameters studied